The Effect of Foot Massage on Peripheral Sensitivity in Patients With Type 2 Diabetes Mellitus Using The Ipswich Touch Test At Rsud Kabupaten Bekasi Hospital in 2025 - Aisyah Istyaningsih; Arifah Rakhmawati; Achmad Fauzi (Universitas Pahlawan Tuanku Tambusai, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder that frequently leads to peripheral neuropathy due to prolonged hyperglycaemia. Peripheral neuropathy is characterized by reduced protective sensation in the lower extremities, particularly the feet, thereby increasing the risk of diabetic foot ulcers and amputation. Prevention of these complications requires early detection and appropriate non-pharmacological interventions. Foot massage is considered a safe and easily applicable intervention, while changes in peripheral sensation can be assessed using the simple and reliable Ipswich Touch Test (IpTT).This study employed a quantitative pre-experimental design with a one-group pretest–post test approach. The sample consisted of patients with Type 2 Diabetes Mellitus receiving outpatient and inpatient care at Bekasi District General Hospital. Participants received foot massage according to standard procedures. Peripheral sensation was assessed before and after the intervention using the Ipswich Touch Test. Data were analysed using the Wilcoxon Signed Rank Test to evaluate differences in peripheral sensation before and after the intervention.There was a statistically significant difference in peripheral sensation scores before and after the foot massage intervention. Post-intervention findings showed an increase in the number of respondents with normal peripheral sensation based on IpTT results. The Wilcoxon test yielded a p-value of 0.002 (p < 0.05), indicating that foot massage had a significant effect on improving peripheral sensation in patients with Type 2 Diabetes Mellitus. Foot massage significantly improves peripheral sensation in patients with Type 2 Diabetes Mellitus as measured by the Ipswich Touch Test. This intervention may serve as a supportive non-pharmacological therapy in preventing peripheral neuropathy and diabetic foot ulcers. Incorporating foot massage as an independent nursing intervention in clinical practice is recommended. Future studies should employ more rigorous research designs, larger sample sizes, and comparisons with other non-pharmacological interventions to produce more comprehensive evidence.